(3fMh GdbdhHs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdfMh YHGQI Yf GdbUO hGdfGS eNJdahf ai GdebGUO hjJaQbhf ai GdehGQO hGdeUGOQ s
(3BNQgG (B:s
(3MQha GdLQ JNaV GdCSeGA adeG Yde GdeMbbhf Cf GdEfTGA HGddg hef Gddg hEdi Gddg NaVhG CfaSge JhGVYkG ddg Je cJGH fMh GdbdhH HMeO Gddg hYhfg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1935s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha JjehQ (B196) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs